Feminist reconstructions of Christian doctrine : narrative analysis and appraisal - Greene-McCreight, Kathryn, 1961- (Oxford University Press, 2000)
What is the relationship between feminist theology and classical Christian theology? Is feminist theology "Christian," and if so, in what respect and to what extent? This study seeks to analyze and evaluate the relation of feminist "reconstructions" to traditional Christian teaching. Greene-McCreight uses the extent to which the biblical depiction of God is allowed to guide theological hermeneutics as a test of orthodoxy. She looks at the writings of a wide range of contemporary feminist theologians, discusses their doctrinal patterns, and demonstrates how the Bible is used